Unicorn (Rowan Tree Church) [5], [no. 4] (Eostara, 1982) - Rowan Tree Church (Rowan Tree Church Periodicals Collection, New Age Movements, Occultism, and Spiritualism Research Library. Archives and Special Collections, 2020, 1982)
Happy Horn Blessings! / Andrius -- Notes From an Herbal: [Herbs and their God and Goddess Associations] -- Today We Rise / Poem by Prairie Jackson -- [Little Gidding last stanza] / T.S. Eliot -- A Story. [part 1] / by Sil -- Positive Magic by Marion Weinstein / Review -- Announcements -- We've Moved!! / Evanstar Bookstore -- Contacts -- Extra Pages Survey Results
1 Electronic record(s) and derivatives. 8710492 bytes. 17 pages.
Keywords: Plants--Mythology; Rowan Tree Church; Extra pages (Rowan Tree Church); Poetry; Book reviews; Newsletters